Managerial Entrenchment and the Choice of Debt Financing - Sy, Amadou (IMF Working Papers; Working Paper, 1999)
The paper analyzes the choice between public and private debt by an entrenched manager. The model shows that when the firm's credit risk is low, management issues public bonds because of the value gains from increased flexibility rather than reduced restrictions and monitoring. In fact, management's expected private gains decrease as initial private debt restrictions are selectively relaxed. In contrast, when credit risk is high, management issues private debt because of the value gains and private benefits from renegotiating more stringent restrictions. When the maturity of private debt is shortened, however, privately and publicly placed bonds can be preferred to bank debt.